Indigenous Resistance to Reserves Reductions during the Late Colonial Period in Northeast New Granada - Pita Pico, Roger (2022)
This article analyzes the resistance put forward by indigenous communities to the policy of reducing reservations implemented by the viceregal government in the northeast of the New Kingdom of Granada during the 18th and early 19th centuries. The improvisations and arbitrariness committed in these official proceedings affected the native communities that each time saw their spaces limited and their possibilities to claim their rights in the face of the growing power exercised by the white and mestizo layer in their aspirations to occupy more territory and organize. through the erection of parishes. Given this, the indigenous saw how inter-ethnic conflicts with free neighbors increased, in addition to which they experienced a progressive uprooting and disintegration as ancestral communities.